A rare case of obstructed hemivagina and ipsilateral renal agenesis syndrome presented with haematocolpos and haematometra - Devi, Auxeelia Packia; Diana, Valsa; Kumar, Geetha M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Obstructed hemivagina and ipsilateral renal anomaly (OHVIRA) syndrome is a syndrome characterised by obstructed hemivagina, ipsilateral renal agenesis and uterine didelphys. It is a rare congenital anomaly results from defective fusion of the Müllerian ducts during development of the female reproductive system. It is also known as Herlyn-Werner-Wunderlich syndrome. Aim of the study was to project a rare case of developmental anomaly of Mullerian system. OHVIRA syndrome is rare anomaly. The most common presentation of this syndrome is a mass secondary to hematocolpos, pain, and dysmenorrhea. Incidence rate is 0.1-3%. Other symptoms are swelling of the abdomen, nausea and vomiting due to pelvic pain, and fertility may also be affected. Diagnosed by magnetic resonance imaging (MRI) and ultrasound. This case was managed by diagnostic laparoscopy with resection of vertical vaginal septum. Other treatment option is vaginoscopic incision of the oblique vaginal septum. High level of clinical suspicion and early surgical intervention will prevent further complications.